Pengaruh RGEC Dan Variabel Makroekonomi Terhadap Banking Distress Dengan Menggunakan CD Indeks Di Indonesia - PRIANTI, FEBBY; MUSDHOLIFAH, (Jurnal Ilmu Manajemen (JIM), 2018)
Abstract The bank is financial institutions that collect funds from society and distribute those funds for credit and providing other banking services. As financial intermediaries, a bank cannot be separated from external and internal factors which can cause banking distress. This study aimed to examine the influence of internal banking factors and macroeconomic variables for predicting banking distress in Indonesia using Crisis and Default Index. The internal variable used in this study are risk profile proxied by NPL and LDR; good corporate governance with a proxy of the size of board directors; earnings proxied by ROA, ROE, BOPO, NIM; as well as capital proxied by CAR. While the macroeconomic variables used are economic growth and inflation.This study used 28 conventional banks in Indonesia as sample and logit analysis during 2010-2016.The result of the research shows that the internal factor of size of board directors has a positive effect on the prediction of banking distress while ROE negatively affects the prediction of banking distress. This is important to be done by the internal banking in maintaining the level of profitability and manage good corporate governance by taking into account various factors that are inaugurated as an effort to minimize the probability of banking distress.In macroeconomic factors, the variable of GDP and inflation did not significantly influence the prediction of banking distress due to the internal fundamentals of the banking system in facing the changing macro condition. Keywords: Banking distress, Crisis and Default Index, RGEC, macroeconomics, logistic regression.